ANALISIS SUPPLY CHAIN MANAGEMENT PADA PT. MONIER DI SIDOARJO - Moh Afrizal Miradji (UMSurabaya Publishing, 2014)
Supply Chain Management covers all the activities since material came from the supplier, then the material was processed into semi-finished products or finished products until the product is distributed to consumers. To know the performance of the company's Supply Chain, measurement is needed. From these measurements will be obtained result, so good or not good performance of the company's Supply Chain can be seen and can find the weaknesses of existing systems to be repaired. Given a good supply chain performance, the performance the company will increasingly focus and provide benefits, whether for the company, suppliers, and consumers. This study used qualitative data. The scope of analysis in this research is related to supply chain management functions in PT Monier Sidoarjo, in the implementation of financial and operational audits. Source data is data obtained directly by the author in the research by conducting surveys and meetings as well as direct interviews with relevant parties. Research findings stating that in terms of financial, SCM can then be to increase profits at the company, but companies need to conduct operational checks on the production function, attention and immediate action to factors that cause a lack of efficiency and effectiveness of the production function is the lack of communication between the sales and production, delays in receiving raw materials, production planning and scheduling patterns. Companies need to perform the separation function explicitly against a concurrently-a concurrently functions, provide either a separate storage area for raw materials, intermediate goods and production results, and conduct internal documents that are supposed to exist in order to improve the internal control system and can provide adequate protection against corporate wealth Organizations need to separate